Combating Child Marriage: A Comparative Analysis of Regulations in Indonesia and The Philippines (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
Legal discrepancies regarding child marriage are apparent in the divergence between the legislation forbidding underage unions and the actual practices observed. Despite the elevation of the age restriction, the leniency with which courts issue marital dispensations, particularly in instances of out-of-wedlock pregnancies, engenders inconsistency in legal enforcement, hence perpetuating injustices against children's rights. The study topic aims to analyze the comparative distinctions in the legal frameworks of Indonesia and the Philippines concerning child marriage. This study aims to investigate and compare the legislative frameworks regulating child marriage in Indonesia and the Philippines, highlighting their differences and similarities. The study concept and methodology employ a qualitative approach utilizing a comparative legal framework. The analytical method employed is normative legal analysis. The research findings suggest that granting marital dispensations that violate child protection principles may also breach the Child Protection Act, which seeks to provide the highest level of safeguarding for children against all types of abuse, exploitation, and discrimination. Indonesia and the Philippines are encountering distinct hurdles in tackling this problem. Indonesia has established a dispensation system permitting child marriage under certain circumstances, but the Philippines has enacted a complete prohibition on child marriage. The legislation forbids child marriage and enforces more severe penalties for anybody who participates in or enables it. The Philippines' prohibition of child marriage signifies a substantial step in the nation's struggle against this detrimental practice.